Elimination of polycyclic aromatic hydrocarbons in light cycle oil via hydrogenation over NiMo-based catalysts - Sangjun, Peeranat; Nuangjumnong, Sippawich; Hunsiri, Warodom; Hongkailers, Surachet; Hinchiranan, Napida (Science, Engineering and Health Studies, 2024)
Light cycle oil (LCO) is a by-product obtained from the fluid catalytic cracking unit in petroleum refineries. Since LCO has a high content of organosulfurous compounds and polycyclic aromatic hydrocarbons (PAHs), which adversely affect the environment and animals, LCO cannot be directly applied in combustion engines. To utilize LCO as a higher value-added chemical, this work aimed to transform the PAHs in LCO into aromatics with a lower toxicity, such as BTX (benzene, toluene, and xylene), tetralins, and decalins, via hydrogenation over nickel (Ni)–molybdenum (Mo)-based catalysts. The effect of the catalyst’s support on the hydrogenation efficiency was investigated using -alumina ( -Al2O3), KIT-6, and -zeolite. The results showed that the NiMo/KIT-6 catalyst exhibited the highest ability for hydrogenation of PAHs (49.6% removal of PAHs) and produced alkylbenzenes, decalins, and tetralins at 12.0, 0.22, and 36.4% selectivity, respectively, when the reaction was conducted under 40 bar hydrogen pressure at 350 C for 3 h with a stirring rate of 300 rpm. This study proposed an alternative way to produce value-added chemicals from a by-product stream derived from the petroleum refinery process, thereby expanding the options for sustainable development.